2010
DOI: 10.1111/j.1478-5153.2010.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of enteral feeding practices in critically ill children

Abstract: This paper highlights the dearth of research related to enteral feeding in critically ill children. We found that the use of feeding guidelines improved calorie delivery and so units should be encouraged to develop their own guidelines based on the best evidence available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…This study found that nutrition is being initiated on average 22.8 hours after admission, which current literature is suggesting is unnecessarily prolonged 1 , 2 . It reveals inconsistent reasons for interrupting and delaying nutrition among health care practitioners and large cumulative caloric deficits over a patient's admission.…”
Section: Clinical Relevancy Statementmentioning
confidence: 77%
See 1 more Smart Citation
“…This study found that nutrition is being initiated on average 22.8 hours after admission, which current literature is suggesting is unnecessarily prolonged 1 , 2 . It reveals inconsistent reasons for interrupting and delaying nutrition among health care practitioners and large cumulative caloric deficits over a patient's admission.…”
Section: Clinical Relevancy Statementmentioning
confidence: 77%
“…‐ 12 Despite the importance of nutrition in the PICU population, prolonged time to initiation, 1 , 10 , 11 frequent and potentially avoidable interruptions, 1 , 13 ‐ 15 and controversies surrounding when to withhold nutrition 16 often result in large deficits in nutrition delivery over the length of a patient's admissions 8 . Implementation of nutrition support protocols has led to earlier initiation and reduced deficits of nutrition delivery in the PICU, especially when continually evaluated and adapted for current best practices 1 , 2 . Large variations exist between practitioners as well as hospitals regarding practices related to prescribed nutrition and barriers to optimal delivery 14 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…These interruptions to EN may result in a nutrient deprivation for a high proportion of the illness course. EN intolerance remains the most commonly reported barrier to optimizing EN intake in the PICU 3,5,6,17 . However, a unifying definition of EN intolerance does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…However, a unifying definition of EN intolerance does not exist. As a result, a variety of clinical signs and symptoms have been used to determine EN intolerance in critically ill children 17 . Gastric residual volume (GRV) is routinely measured in the intensive care environment despite lack of evidence to support it as a useful marker of EN intolerance 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…(68) Surveys have shown that most bedside PICU providers use GRV measurements and feeding algorithms include GRV measurement as a measure of EN intolerance to guide bedside nutrition practices. (7, 69) The accuracy of GRV measurement to predict delayed GE or EN intolerance has not been studied in critically ill children. Furthermore, GRV measurement is complicated by a lack of standardization in the GRV threshold to define EN intolerance and in measurement techniques that are affected by patient posture and the feeding tube properties.…”
Section: Introductionmentioning
confidence: 99%